Pengaruh Metode Resitasi Oleh Guru PAK Terhadap Keaktifan Belajar Siswa Kelas VIII SMP Negeri 4 Sibolga Tahun Ajaran 2023/2024 - Magdalena Simaremare; Dorlan Naibaho; Sabar Rudi Sitompul; Rida Gultom; Johari Manik (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this study was to determine the extent of the Influence of the Recitation Method by PAK Teachers on the Learning Activity of Class VIII Students of SMP Negeri 4 Sibolga in the 2023/2024 Academic Year, with the hypothesis that there is a positive and significant influence of the recitation method by PAK teachers on the learning activity of class VIII students of SMP Negeri 4 Sibolga in the 2023/2024 Academic Year. With a population of all class VIII students of SMP Negeri 4 Sibolga who are Protestant Christians totaling 121 people with a sample of 37 people, this study uses a descriptive method with a random sampling technique. Data were collected with a closed questionnaire of 40 items compiled by the author based on variable indicators according to expert theory. The questionnaire trial was conducted on 30 students of SMP Negeri 4 Sibolga in the 2023/2024 Academic Year using 46 questionnaire questions and after being tested, the results of the validity of the questionnaire trial were found to be rcount = -0.352 - 0.609 (there were 6 question items that had a validity of less than rtable 0.361 so that invalid questionnaires were discarded. Thus, the valid questionnaires amounted to 40 questions. And the reliability of the questionnaire trial which was at a value of 0.899 had been tested for validity and reliability. The results of the data analysis showed that there was a positive and significant influence between the Recitation Method by PAK Teachers on the Learning Activity of Class VIII Students of SMP Negeri 4 Sibolga in the 2023/2024 Academic Year. With the relationship test, it was obtained that rcount> rtable, namely 0.706> 0.325, with a significant relationship test of tcount> ttable, namely 8.319>2.021, with a linear regression test Y ̂ = α+bx = 23.39+0.355X. This equation shows that in a constant state of 26.98, for every addition of variable X (recitation method) by one unit, there will be an increase in variable Y (student learning activity) by 0.355 from (variable X), coefficient of determination 49.84%. This means that Ho is rejected and Ha is accepted. The significant effect test with Fcount>Ftable (34.735>4.08) means that there is a positive and significant effect between the recitation method by PAK teachers on the learning activity of class VIII students of SMP Negeri 4 Sibolga in the 2023/2024 Academic Year. This study suggests that teachers always increase the use of the recitation method in the teaching and learning process, so that class VIII students of SMP Negeri 4 Sibolg are more active in participating in class learning.